Extracting wavelet based neural features from human intracortical recordings for neuroprosthetics applications - Zhang, Mingming; Schwemmer, Michael A.; Ting, Jordyn E.; Majstorovic, Connor E.; Friedenberg, David A.; Bockbrader, Marcia A.; Jerry Mysiw, W.; Rezai, Ali R.; Annetta, Nicholas V.; Bouton, Chad E.; Bresler, Herbert S.; Sharma, Gaurav (Bioelectronic medicine, 2018)
Background Understanding the long-term behavior of intracortically-recorded signals is essential for improving the performance of Brain Computer Interfaces. However, few studies have systematically investigated chronic neural recordings from an implanted microelectrode array in the human brain. Methods In this study, we show the applicability of wavelet decomposition method to extract and demonstrate the utility of long-term stable features in neural signals obtained from a microelectrode array implanted in the motor cortex of a human with tetraplegia. Wavelet decomposition was applied to the raw voltage data to generate mean wavelet power (MWP) features, which were further divided into three sub-frequency bands, low-frequency MWP ( lf -MWP, 0–234 Hz), mid-frequency MWP ( mf -MWP, 234 Hz–3.75 kHz) and high-frequency MWP ( hf -MWP, >3.75 kHz). We analyzed these features using data collected from two experiments that were repeated over the course of about 3 years and compared their signal stability and decoding performance with the more standard threshold crossings, local field potentials (LFP), multi-unit activity (MUA) features obtained from the raw voltage recordings. Results All neural features could stably track neural information for over 3 years post-implantation and were less prone to signal degradation compared to threshold crossings. Furthermore, when used as an input to support vector machine based decoding algorithms, the mf -MWP and MUA demonstrated significantly better performance, respectively, in classifying imagined motor tasks than using the lf -MWP, hf -MWP, LFP, or threshold crossings. Conclusions Our results suggest that using MWP features in the appropriate frequency bands can provide an effective neural feature for brain computer interface intended for chronic applications. Trial registration This study was approved by the U.S. Food and Drug Administration (Investigational Device Exemption) and the Ohio State University Medical Center Institutional Review Board (Columbus, Ohio). The study conformed to institutional requirements for the conduct of human subjects and was filed on ClinicalTrials.gov (Identifier NCT01997125 ).